Impact of Fullerene on the Photophysics of Ternary Small Molecule Organic Solar Cells. Issue 33 (22nd July 2019) - Karuthedath, Safakath; Firdaus, Yuliar; Liang, Ru‐Ze; Gorenflot, Julien; Beaujuge, Pierre M.; Anthopoulos, Thomas D.; Laquai, Frédéric
Abstract: Ternary organic solar cells (OSCs) are among the best‐performing organic photovoltaic devices to date, largely due to the recent development of nonfullerene acceptors. However, fullerene molecules still play an important role in ternary OSC systems, since, for reasons not well understood, they often improve the device performance, despite their lack of absorption. Here, the photophysics of a prototypical ternary small‐molecule OSC blend composed of the donor DR3, the nonfullerene acceptor ICC6, and the fullerene derivative PC71 BM is studied by ultrafast spectroscopy. Surprisingly, it is found that after excitation of PC71 BM, ultrafast singlet energy transfer to ICC6 competes efficiently with charge transfer. Subsequently, singlets on ICC6 undergo hole transfer to DR3, resulting in free charge generation. Interestingly, PC71 BM improves indirectly the electron mobility of the ternary blend, while electrons reside predominantly in ICC6 domains as indicated by fast spectroscopy. The improved mobility facilitates charge carrier extraction, in turn leading to higher device efficiencies of the ternary compared to binary solar cells. Using the (photo)physical parameters obtained from (transient) spectroscopy and charge transport measurements, the device's current–voltage characteristics are simulated and it is demonstrated that the parameters accurately reproduce the experimentally measured device performance. Abstract : Energy and charge transfer in ternary organic solar cells (OSC) are investigated by transient spectroscopy. Depending on the excitation wavelength, either exclusive charge transfer or a competition between energy and charge transfer is observed. The presence of PC71 BM in the ternary OSC increases the absorption in the UV spectral region and indirectly enhances the electron mobility of ICC6 in the blend.